Testing the Digital Health Literacy Instrument for Adolescents: Cognitive Interviews - Park, Eunhee; Kwon, Misol (JMIR Publications, 2021)
BackgroundDespite the increasing number of youth seeking health information on the internet, few studies have been conducted to measure digital health literacy in this population. The digital health literacy instrument (DHLI) is defined as a scale that measures the ability to operate digital devices and read and write in web-based modes, and it assesses seven subconstructs: operational skills, navigation skills, information searching, evaluating reliability, determining relevance, adding self-generated content to a web-based app, and protecting privacy. Currently, there is no validation process of this instrument among adolescents. ObjectiveThis study aims to explore the usability and content validity of DHLI. MethodsUpon the approval of institutional review board protocol, cognitive interviews were conducted. A total of 34 adolescents aged 10-18 years (n=17, 50% female) participated in individual cognitive interviews. Two rounds of concurrent cognitive interviews were conducted to assess the content validity of DHLI using the thinking aloud method and probing questions. ResultsClarity related to unclear wording, undefined technical terms, vague terms, and difficult vocabularies was a major issue identified. Problems related to potentially inappropriate assumptions were also identified. In addition, concerns related to recall bias and socially sensitive phenomena were raised. No issues regarding response options or instrument instructions were noted. ConclusionsThe initial round of interviews provided a potential resolution to the problems identified with comprehension and communication, whereas the second round prompted improvement in content validity. Dual rounds of cognitive interviews provided substantial insights into survey interpretation when introduced to US adolescents. This study examined the validity of the DHLI and suggests revision points for assessing adolescent digital health literacy.